Antipsychotic initiation among adults with intellectual and developmental disabilities in Ontario: a population-based cohort study. Issue 7 (30th July 2019) - Gomes, Tara; Khuu, Wayne; Tadrous, Mina; Vigod, Simone; Cobigo, Virginie; Lunsky, Yona
Abstract : Objectives: To describe factors associated with initiating antipsychotics and patterns of persistence to antipsychotic therapy in a large cohort of adults with intellectual and developmental disabilities. Design: Population-based cohort study. Setting: Ontario, Canada. Participants: Adults with intellectual and developmental disabilities (IDD) in Ontario. Outcome measures: We used multivariable logistic regression to investigate patient characteristics associated with antipsychotic initiation. Patient characteristics studied included sociodemographic characteristics, measures of clinical comorbidity and health service use. Results: Among 39 244 individuals eligible for this study, 6924 (17.6%) initiated an antipsychotic over the accrual window, of whom 1863 (26.9%) had no psychiatric diagnosis in the prior 2 years. A number of factors were significantly associated with antipsychotic initiation, including male gender, residence in a group home, prior use of benzodiazepines, antidepressants or cognitive enhancers, a recent emergency department visit or mental health hospitalisation and a visit to a psychiatrist or family physician in the prior 90 days. In a secondary analysis, the association between antipsychotic initiation and age, prior diagnosis of diabetes or myocardial infarction and polypharmacy differed slightly on the basis of whether an individual had a previously diagnosed psychiatric disorder. Conclusions: Factors associated with the initiation of an antipsychotic differ according to the presence of a psychiatric diagnosis. Given the long duration of antipsychotic use in this population, future research is needed to understand the appropriateness of antipsychotic initiation among adults with IDD and the safety implications of long-term use of these products.